1984
DOI: 10.1002/bjs.1800710727
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenocarcinoma of the vermiform appendix: Report of a series of ten cases, and review of the literature

Abstract: Ten cases of primary adenocarcinoma of the vermiform appendix are presented. The condition is rare and usually presents after middle age as acute appendicitis. It is seldom recognized during appendicectomy. The tumours resemble colonic adenocarcinomas but, because of peculiarities in the anatomy of the appendix, there is a tendency to early local spread. Right hemicolectomy performed as soon as the true nature of the lesion is recognized is the treatment of choice and has been shown to improve survival. Even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The reason for this is its anatomical position which is a side tract to the direct intestinal passage. Thus, the usual symptoms of intestinal tumors such as mechanical ileus and/or melena occur only in advanced stages [20], In a series of middleaged to elderly patients, abdominal pain and a palpable mass in the right lower quadrant were the leading symp toms [21]. Hematuria, [5,7,10,12], as in our patient, and recurrent urinary tract infection emanating from an enterovesical fistula [13] point out involvement of the blad der.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is its anatomical position which is a side tract to the direct intestinal passage. Thus, the usual symptoms of intestinal tumors such as mechanical ileus and/or melena occur only in advanced stages [20], In a series of middleaged to elderly patients, abdominal pain and a palpable mass in the right lower quadrant were the leading symp toms [21]. Hematuria, [5,7,10,12], as in our patient, and recurrent urinary tract infection emanating from an enterovesical fistula [13] point out involvement of the blad der.…”
Section: Discussionmentioning
confidence: 99%
“…Other less common modes of presentation include a palpable mass, obstruction, gastrointestinal bleeding, or symptoms related to metastases. 7,8,[51][52][53][54][56][57][58][59][61][62][63] Pathology Appendiceal adenocarcinomas are classified as adenocarcinoma not otherwise specified, mucinous adenocarcinoma, signet ring cell adenocarcinoma, and undifferentiated carcinoma. 14 Mucinous adenocarcinoma accounts for B40% of all appendiceal adenocarcinomas although it is unclear what proportion of these might be classified as LAMN according to current WHO terminology.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…57,58,62 Several studies have shown that histologic grade 8,49,61 and Duke's stage correlate with prognosis. 8,57,58,61,62,68,69 Patients with peritoneal carcinomatosis have a poor prognosis. 10,52,60,62 Treatment Invasive adenocarcinoma of the appendix warrants treatment by right hemicolectomy, with lymph node dissection, in order to stage the tumor and ensure complete resection.…”
Section: Natural Historymentioning
confidence: 99%
“…Despite some earlier theories [134], there is no relationship between appendicectomy and malignancy in general [135], or colorec tal carcinoma in particular [136], Occasional patients are found to have tumours of the appendix itself on histological examination; carcinoid tumours can usually be treated conservatively, but adenocarcinomas require re-operation and a right hemicolectomy [112,137],…”
Section: Malignancymentioning
confidence: 99%